2014
DOI: 10.3109/21678421.2014.905606
|View full text |Cite
|
Sign up to set email alerts
|

Limited role of free TDP-43 as a diagnostic tool in neurodegenerative diseases

Abstract: TAR DNA-binding protein 43 (TDP-43) is one of the neuropathological hallmarks in amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). It is present in patients' blood and cerebrospinal fluid (CSF); however, the source and clinical relevance of TDP-43 measurements in body fluids is uncertain. We investigated paired CSF and serum samples, blood lymphocytes, brain urea fractions and purified exosomes from CSF for TDP-43 by one- (1D), and two-dimensional (2D) Western immunoblotting (WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 34 publications
3
90
1
Order By: Relevance
“…When detected with phospho-independent antibody, plasma TDP-43 level is not significantly different between FTLD and AD, with or without TDP-43 pathology; when detected with phospho-dependent antibody, plasma TDP-43 level is higher in patients with TDP-43 pathology than in those without TDP-43 pathology in FTLD, but this phenomenon is not found in AD patients [44]. Recent study finds that the concentration ratio of TDP-43 CSF to blood is about 1:200, suggesting that CSF TDP-43 may originate from blood [45].…”
Section: Plasma and Csf Levels Of Tdp-43 In Admentioning
confidence: 82%
See 1 more Smart Citation
“…When detected with phospho-independent antibody, plasma TDP-43 level is not significantly different between FTLD and AD, with or without TDP-43 pathology; when detected with phospho-dependent antibody, plasma TDP-43 level is higher in patients with TDP-43 pathology than in those without TDP-43 pathology in FTLD, but this phenomenon is not found in AD patients [44]. Recent study finds that the concentration ratio of TDP-43 CSF to blood is about 1:200, suggesting that CSF TDP-43 may originate from blood [45].…”
Section: Plasma and Csf Levels Of Tdp-43 In Admentioning
confidence: 82%
“…Because of the low concentration of TDP-43 in CSF compared to blood, no such relation between CSF TDP-43 and clinical phenotype has been reported [45]. A study indicated that CSF levels of many analytes including Fas, neuropeptides, and chemokines are different between FTLD-TDP and FTLD-tau, and the classification analysis in the autopsy cohort shows high sensitivity for FTLD-TDP (86 %) and modest specificity (78 %) [46].…”
Section: Csf Tdp-43 In Admentioning
confidence: 94%
“…Although initially thought to exist as an intracellular/intranuclear protein, studies by ELISA and Western blotting have shown that it is detectable in the extracellular fluids, such as CSF and human plasma [32]. In CSF it may originate from blood [33] or from neural cells [18]. Compatible with the latter hypothesis, no disruption of the blood-brain barrier could be detected in our cohort, as assessed by normal albumin index in both patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…CSF EVs from patients with AD have abnormally high levels of phosphorylated tau (79), while those from patients with MS have high levels of isolectin B4 (IB4), which is associated with neuroinflammation (80). CSF EVs from patients with ALS have elevated TDP-43 (81). Increased levels of the PD-associated proteins deglycase DJ-1 and leucine-rich repeat kinase 2 (LRRK2) have been found in bloodderived EVs in patients with PD (82,83).…”
Section: R E V I E W S E R I E S : E X T R a C E L L U L A R V E S I mentioning
confidence: 99%